FACTORS INFLUENCING PURCHASING DECISIONS ON NIKE SHOES (CASE STUDY OF FEB STUDENTS OF BANDAR LAMPUNG UNIVERSITY) - Refael Gustiawan; Herry Goenawan Soedarsa (ZILLZELL MEDIA PRIMA, 2024)
The shoe market is currently experiencing increased competition. Each brand creates high-quality sneakers. The shoe brand